Experiences of transwomen individuals in accessing oral health care in a low and middle-income country: a qualitative study from Pakistan - Anhum Haroon Jadoon; Muhammad Shahzad; Saad Ishaq Khattak; Askar Ali; Hannah Maria Jennings; Maria Ishaq Khattak (BMC Public Health)
Abstract Objective Transwomen are one of the most marginalised groups globally, with their experiences of prejudice significantly impacting their access to dental care and leading to social isolation. This study aimed to explore the experiences of transwomen in accessing oral health care services in Khyber Pakhtunkhwa, Pakistan. Methods A qualitative phenomenological study design was utilised to gain in-depth insights. Eight transwomen were purposively recruited from the districts of Haripur, Abbottabad, and Mansehra in the Hazara division of Khyber Pakhtunkhwa, Pakistan. Semi-structured interviews were conducted in Urdu, transcribed, and translated. A descriptive approach was utilised for thematic analysis. Results The analysis revealed several barriers faced by transwomen in accessing oral health care, organised into key themes: (1) Healthcare discrimination and marginalisation, (2) Quality of care and dental professionals’ attitudes, (3) Cost and affordability of dental care, (4) Social stigma and absence of community support, and (5) Inclusive dental care facilities. Conclusion This research highlights barriers faced by transwomen in Pakistan when accessing dental care, leading to delayed treatment and poor oral health outcomes. Financial constraints and a lack of empathy from dental professionals further exacerbate these challenges. Participants recommended policy reforms such as anti-discrimination laws, separate waiting rooms, and counters to improve access. These findings underline the need for policymakers to create inclusive dental service systems tailored to the needs of transwomen.